2016
DOI: 10.1007/978-3-319-32023-6_6
|View full text |Cite
|
Sign up to set email alerts
|

Discotic Liquid Crystals for Self-organizing Photovoltaics

Abstract: Development of photovoltaic solar cells using organic materials as active components is an emerging area of contemporary research endeavor toward sustainable energy harvesting. Among the organic optoelectronic materials, disc-shaped polycyclic aromatic compounds capable of exhibiting columnar liquid crystal (LC) properties are unique. Liquid crystalline materials simultaneously display the anisotropic properties of crystalline solids and flow properties of isotropic liquids. The order and dynamics of the molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 106 publications
0
6
0
Order By: Relevance
“…The first observation of the photovoltaic effect in DLC was reported by Gregg et al [ 218 ], who observed the photovoltaic properties of a phthalocyanine derivative in symmetric cells. A review of the results obtained using DLC in the field of OSC can be found in reference [ 219 ], while the newest results will be presented here. Bajpai and coworkers studied how the presence of a layer of the 2,3,6,7,10,11-hexabutyloxytriphenylene mesogen can influence the performance of the classic bulk-heterojunction OSC formed by poly (3-hexylthiophene) and [ 6 , 6 ]-phenyl-C61-butyric acid methyl ester (P3HT:PCBM) [ 220 , 221 ].…”
Section: Recent Advances In the Study Of Discotic Liquid Crystalsmentioning
confidence: 99%
“…The first observation of the photovoltaic effect in DLC was reported by Gregg et al [ 218 ], who observed the photovoltaic properties of a phthalocyanine derivative in symmetric cells. A review of the results obtained using DLC in the field of OSC can be found in reference [ 219 ], while the newest results will be presented here. Bajpai and coworkers studied how the presence of a layer of the 2,3,6,7,10,11-hexabutyloxytriphenylene mesogen can influence the performance of the classic bulk-heterojunction OSC formed by poly (3-hexylthiophene) and [ 6 , 6 ]-phenyl-C61-butyric acid methyl ester (P3HT:PCBM) [ 220 , 221 ].…”
Section: Recent Advances In the Study Of Discotic Liquid Crystalsmentioning
confidence: 99%
“…In such a scenario, organic electronic materials have an upper hand over their inorganic counterparts in terms of reduced synthetic costs as well as reduced toxicity. With organic light-emitting diodes (OLEDs) already flourishing in the market, 1,2 and organic photovoltaics (OPVs), sensors and organic field-effect transistors (OFETs) gradually emerging as the next generation of technology, the need for lightweight and flexible devices for the global populace is becoming evident with each passing day. The effective operations of all these devices rely on the charge transporting abilities of organic semiconductors (OSCs) as the key functional parameter.…”
Section: Introductionmentioning
confidence: 99%
“…Functional groups, such as azobenzene [ 10 ] or other conjugated moieties [ 11 , 12 ], can be introduced for tailoring of the surface or bulk properties of triphenylene-based materials. Besides the extensive studies on the photophysical [ 13 ] and charge transport properties [ 14 ] of H n Ts, which are crucial for their implementation in organic light-emitting diodes (OLEDs) [ 15 ], organic field-effect transistors (OFETs) [ 16 ], or organic photovoltaics (OPVs) [ 17 ], several aspects connected with molecular order and thin film engineering have been investigated. Due to the liquid-like properties of DLCs, a large amount of studies are concentrated on the self-assembly of H n Ts in thin films [ 18 ], under geometrical confinement [ 19 ], or the growth of nanostructures of different dimensionality [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since the fabrication of organic active layers for optoelectronic devices preferably involves solution processing, e.g., spin coating [ 16 , 17 , 18 ], knowledge about the behavior of molecules in solution is highly desirable. The aggregation has a great influence on the electronic properties of solutions of polycyclic aromatic molecules, since functionalities often arise due to electronic coupling between π -conjugated systems [ 24 ].…”
Section: Introductionmentioning
confidence: 99%